Molecular effects of intermittent stress on primary feline uroepithelial cell culture as an in vitro model of feline idiopathic cystitis - Hatala, Patrícia; Sebők, Csilla; Mackei, Máté; Kárpáti, Karina; Gálfi, Péter; Neogrády, Zsuzsanna; Mátis, Gábor (Frontiers in Veterinary Science, 2023)
The most common cause of feline lower urinary tract disease (FLUDT) is feline idiopathic cystitis (FIC), which is a complex multifactorial disease with symptoms including stranguria, dysuria, hematuria, and pain during urination. The development of these symptoms is often triggered by stress, and in case of chronic stress, these symptoms will many times return. One of the most important stress hormones in the pathogenesis of FIC is norepinephrine (NE), as persistently elevated level of this hormone can be measured in the blood of cats with FIC. However, it is not well understood if recurrently elevated level of NE has any direct effect on urinary bladder, therefore the aim of this study was to investigate the molecular effects of intermittent NE exposure on feline primary uroepithelial cell culture. Primary uroepithelial cells were gained from the mucosa of the bladder of a euthanized cat, and were cultured for 6 days, then they were exposed to 10, 100, and 1000 µM NE treatment for 3x1 h, including a 1h long regeneration period between exposures. NE was able to trigger pro-inflammatory response and oxidative-stress in the uroepithelial cells by increasing the level of stromal cell derived factor 1 (SDF-1) and H2O2 in cell culture media. In addition, NE increased the permeability of the uroepithelium, since decreased glycosaminoglycan (GAG) concentration, tight junction protein claudin-4 content, and TER values were measured after the NE treatments. Based on these results it can be concluded that recurrent stress mimicked by 3x1 h NE treatment has a direct molecular effect on the uroepithelial cells, which leads to inflammatory response, oxidative stress and decreased barrier function of the uroepithelium. Therefore, intermittent release of NE may have an important role in the pathogenesis of FIC and the results of this study may contribute to a better understanding of the development of this illness.